Health status for urban trees - A case study of urban trees within Tabuan Jaya Recreational Park - Goh, Khia Leng (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Urbanization creates significant changes in land use and land cover, structure, pattern and function of the ecosystem. Proper landscape planning in urban green spaces is crucial to the creation of urban forestry system that is closely associated with the city dwellers. Urban trees play an important in landscape beautification, in reduction of air pollution, moderating local climate, sequestering carbon and has significant contribution towards aesthetic va'lues and ecosystem The main objective of the study was to calculate the species diversity of urban trees and also to evaluate the health status of trees planted within Tabuan Jaya Recreational Park. A total of 260 trees belonging to 25 species were recorded growing in Tabuan Jaya Recreational Park. Sygyzium campanulatum with 67 trees: 25.77% was the major species planted followed by Roystonea regia with 47 trees: 18.08%, Ptychosperma macarthurii with 36 trees: 13.85%, Spathodea companulata with 12 trees: 4.62%, Pometia pin nata with 11 trees: 4.23% and more. Species Diversity Index (SOl) of urban trees planted at Tabuan Jaya Recreational Park was 7.22. The characteristics of tree species planted and the management issues were discussed.